Emission characteristic of small diesel engine fuelled by preheat biodiesel - Isha Mudin, Azim (2015)
The viscosity of fuels has important effects on fuel droplet formation, atomization, vaporization and fuel–air mixing process, thus influencing the exhaust emissions and performance parameters of the engine. The higher viscosity has effect on combustion and proper mixing of fuel with air in the combustion chamber. The aim of this present research was to investigate the effects of preheated biodiesel derived from Waste Cooking Oil and Jatropha (B5, B10 and B15) at 40oC, 50oC and 60oC on emissions of small diesel engine at three different duration of time, which are 40minutes, 80 minutes and 120 minutes. HATZ-DIESEL 1B30 small diesel engine was used in this research. The result show all biodiesel with preheat temperature show increased in exhaust temperature. However the increase of exhaust temperature still lower compare to standard diesel fuel. For gas emission analysis, it found NOx, smoke opacity was decrease compare to diesel fuel as preheat temperature rise at 60oC. There are increase in CO2 emission level as biodiesel blending ratio increase due to oxygen content in biodiesel and its blend.